Mindfulness Intervention to Enhance Happiness for Working People - Pumkhem, Panizzara; Phra Medhivajarapundit; Maechee Narumon Jiwattanasuk (The Journal of International Buddhist Studies College, 2025)
This article aimed to study (1) the key factors that enhance happiness for working people, (2) mindfulness practice for promoting those key factors, and (3) the process of mindfulness intervention to enhance happiness for working people. This study employed a qualitative research method. The instrument for collecting data was documentary research and in-depth interviews with 6 key informants. The research results were found as follows; 1. The key factors that enhance happiness for working people included emotional regulation, job satisfaction, work-life balance, supportive leadership, and mindfulness. These factors were identified through extensive documentary research, including scholarly articles and organizational psychology models. The integration of traditional Buddhist teachings and modern psychological theories provided a holistic perspective on workplace happiness. 2. The study found that mindfulness practices significantly contribute to enhancing the key happiness factors. Practices such as mindful breathing, meditation, and awareness of the present moment were shown to improve emotional resilience, focus, and job satisfaction. Documentary research and studies on Buddhist texts, especially the Four Foundations of Mindfulness, confirmed the relevance and applicability of mindfulness-based interventions (MBIs) in the workplace. These interventions not only reduce stress but also promote a positive emotional climate within professional settings. 3. The final phase, qualitative research through interviews, revealed real-world applications of mindfulness in professional environments. Interviews with seven professionals across various industries demonstrated how mindfulness has been successfully integrated into daily routines. Synthesizing these findings, the study proposes a practical and adaptable mindfulness intervention model that emphasizes simplicity, sustainability, and alignment with both personal development and organizational culture. This model highlights the potential of mindfulness-based approaches as effective strategies to foster happiness and well-being among working populations